Perkembangan Pola Persebaran Real Estate di Wilayah Sub-urban - Githa Stacy; Shirly Wunas; Arifuddin Akil (Department of Urban and Regional Planning, Faculty of Engineering, University of Hasanuddin, 2019)
The Makassar City area tends to lack vacant land, so it becomes very scarce and competition for land occurs. Developers began to glance at vacant land outside Makassar City by expanding vacant land in suburban areas around the center of sungguminasa city, Gowa Regency. The increase in real estate development in suburban areas causes early symptoms of the urban sprawl phenomenon. This study aims to identify developments in the spatial distribution pattern of real estate in suburban areas and arrange directions for developing patterns of distribution of suburban real estate. The analytical method used is comparative analysis, spatial analysis and qualitative and quantitative descriptive analysis. The analysis shows that the distribution of real estate tends to provide an urban sprawl phenomenon. This is because, the spread of real estate is horizontal and monofunctional in nature which results in land wastage with a building density of> 25 units / Ha and a basic coefficient of buildings> 50%. In general, real estate development is in the form of a single building with low accessibility (only one main access). Real estate developments are spatially linear (following the road network) and jumping (separated by distances> 500-1000m). The direction of developing the pattern of distribution of real estate is directed by implementing multilevel residential development mixed with other land functions, as well as the development of environmental TOD-based areas in the real estate area of ​​the sub-urban area.